Functional loading validation method of a wireless three-axis force sensor integrated into a cycling pedal - Chevallier, T.; Fradet, L.; Boucher, J.-P.; Segol, M.; Vignais, N. (Sports Engineering, 2026)
This study aimed to propose and apply a validation method for a novel three-axis force sensor integrated into a cycling pedal, which offers several innovative features, notably compatibility with any bike or stationary cycle and fully wireless operation. A measurement rig was designed to compare the outputs of the pedal forces sensor with those of a reference sensor. A functional loading protocol—during which the pedal forces sensor was tested in seven different orientations—was performed to assess the pedal forces sensor validity in both directions of each axis. Data from the pedal forces sensor and the reference sensor were compared using difference plot, mean bias, intra-class correlation, correlation coefficient and root mean squared error. The maximum root mean squared error was observed for the normal axis (20 N). The validation method indicates that the pedal forces sensor demonstrated excellent agreement with the reference sensor for foot pedal reaction forces measurement and could be adapted to other force sensors.